Examining the inaccurate reproductive health messaging of crisis pregnancy centers: A comparative qualitative study - Evangeline Warren; Alexandra Kissling; Alison H. Norris; Priya R. Gursahaney; Maria F. Gallo (PLoS ONE, 2025)
Objectives Given the prevalence of inaccurate or misleading health messaging linked to crisis pregnancy centers (CPCs) in the literature, we sought to understand what role, if any, standardized training materials might play in perpetuating common themes in reproductive health misinformation. Study design We identified inaccurate health messages present in qualitative interviews with 10 staff members from 8 CPCs in Ohio. Separately, we conducted a content analysis of training manuals from two parent organizations, Care Net and Heartbeat International, to understand the form and substance of inaccurate health information messages in official CPC training materials. We compared the content of the two data sources to identify themes common to both, representing both individual and institutional level dissemination of false health messages. Results We found that parent organizations provide false and misleading information in their training materials, often presenting such information as factually true or accurate. In interviews with a self-identified researcher, CPC staff relayed similar inaccurate health messages about the dangers of abortion and contraception, efficacy of condoms, and causes of infertility, strongly endorsing this false information. As an incidental finding, we documented enthusiasm for dissemination of inaccurate health information by CPC staff members who engage in public outreach and education. Conclusions We found clear similarities in the inaccurate health messages provided by staff to researchers and the official training documents published by the CPC parent organizations. Parent organizations, therefore, may represent a potent source of reproductive health misinformation.